Training medicine students for care in the family health strategy: the professional interpersonal relationship - Veiga Martines, Wânia Regina; Machado, Ana Lúcia (O Mundo da Saúde, 2010)
This study aimed at describing experiences related to Medicine students training from University Center São Camilo, specifically as regards the professional interpersonal relationship and having as object in-service practical activities that occur in the Basic Units of Health of the Family Health Strategy (ESF) in the city of São Paulo. The experience report is based on the training of three groups of second semester students in the period 2008-2010. We propose theoretical lessons and practical works aimed at some modalities of care with an emphasis in basic nursing procedures by means of the disciplines Academy-Teaching Integration and Community II. We observed that the specific investment in the notions of professional interpersonal relationship and communication has facilitated what we consider to be the increasing process of relational learning, at the moment the student has to approach the people who compose the care scenery: users, families, professionals and people in general. The acquisition of relational abilities is characterized as essential to develop the many abilities related to procedures, and over all to support extended care giving in the ESF, which has integral assistance as a guiding principle, all of them activities in which the students take an active part throughout the semester.